(untitled) (BIRDEM Medical Journal, 2013)
Antiphospholipid syndrome (APS) manifests clinically as recurrent venous or arterial thrombosis and/or fetal loss. Diagnosis requires a high index of suspicion during evaluation of women with recurrent pregnancy loss and vascular thrombosis. Low dose aspirin combined with heparin can reduce morbidity and improve the pregnancy outcome. Here we report a case of a 22 year old lady having APS who presented with arthritis, recurrent miscarriages and venous thrombosis. Birdem Med J 2013; 3(1): 44-46 DOI: http://dx.doi.org/10.3329/birdem.v3i1.17126